The Construction of Beauty among University Students - M Edy Susilo (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
This study investigates the meaning construction of beauty among university students. Woman boy has turned into valuable commodity. Capital owners have taken advantages of this condition. Through media, they construct and define the new meaning of beauty. Instead of rejecting this situation, some women, especially adolescence, tend to follow what has been offered by the media and beauty industries and fall into what is called 'fetishism. Through symbolic interaction and social construction theories, this study attempted to analyse how university students construct the meaning of beauty and to what extent the fetishism had occurred. Keywords: beauty, meaning construction, fetishism